Portraying Hikayat Learning For Senior High School In 4.0 Era - Dewi Herlina; Adlina Adlina; Pungky Habib Bachtiar; Fitri Nura Murti (Pancaran Pendidikan, 2019)
Hikayat is one of the learning materials in senior high school. Inside the textbook, it is usually presented with a long narrative text to find the values. In 4.0 era, hikayat is of the concern. Inside it, there are moral values that needed to be preserve and an example for the student. Therefore, portraying hikayat learning needs to be known as a foundation in developing hikayat learning. This research has purposes to know how is hikayat learning in senior high school in the context of 4.0 era. The research objects are the teacher and the students of tenth grade senior high school 2 Jember. This research is using descriptive qualitative model with three data analysis which is observation, interview, and questionnaire. Based on the observation results, the teacher problem in teaching hikayat is language. The dictionary of Melayu-Indonesia is not fully provided that makes students difficult to understand the hikayat. The questionnaire result showed that hikayat learning is not attractive and can’t move with the flow of time.